Forest management and conservation of faunal diversity in Italy: a review. (2nd November 2021) - Amori, Giovanni; Mazzei, Antonio; Storino, Pierpaolo; Urso, Salvatore; Luzzi, Giuseppe; Aloise, Gaetano; Gangale, Carmen; Ouzounov, Dimitar; Luiselli, Luca; Pizzolotto, Roberto; Brandmayr, Pietro
Abstract: We re-examined the knowledge on the relationships between fauna and forest management in Italy. We focused our attention on Vertebrates, including small mammals (Rodents and Soricomorphs), bats, birds, reptiles and amphibians, and on carabid and saproxylic beetles. We found that nearly all groups respond in accordance with Angelstam's scheme of the traditional forestry cycle, with open habitat specialists followed by generalists and forest specialists when pristine conditions have been attained, though with some differences for some taxa. In all groups, some forest "superspecialists" or old growth indicators could be found, in (sub)Mediterranean forests some carabid beetles could be defined as "dendrophilous, " i.e. associated with the presence of old trees. Poplar plantations are poor substitutes for native forests, as well as exotic conifers. We propose a model for an ideal forest structure that may efficiently preserve the faunal components, at the microscale level this coincides with the structure of an unmanaged old growth forest stand, marked also by a deep and humus-rich soil layer. Some caveats at the landscape scale have dealt with in relation to the size of the designed area, in order to avoid fragmentation effects. A sustainable harvesting scheme has indicated in the "systemic silviculture" proposed by Ciancio and other scientists. Graphical abstract: